Hybrid FRP jacketing for enhanced confinement of circular concrete columns in compression - Ribeiro, Filipe Jorge Teixeira (2018)
The main goal of the study herein described was to evaluate the performance of an innovative confining unidirectional hybrid FRP solution for circular concrete columns, exploiting the hybrid effect and pseudo-ductility of FRP jackets made of different fibres. First, an experimental study on the compressive stress-strain curves of small-scale plain circular concrete columns confined with hybrid FRP was conducted. Jackets were produced with dry unidirectional fabrics of high-modulus carbon, standard-modulus carbon, E-glass, and basalt. Different combinations were tested, varying the number of layers of each material. Next, two new simple design-oriented models were developed in order to predict the compressive peak stress of compressed concrete columns confined with hybrid FRP jacketing. Predictions were in close agreement with test results. Finally, an existing analysis-oriented model developed for non-hybrid FRP-confined concrete was adapted to also predict dilation and the compressive stress-strain curve of hybrid FRP-confined concrete. Likewise, predictions were in close agreement with test results. It was concluded that hybridisation can effectively contribute to maximize the lateral strain efficiency of FRP jacketing and its behaviour can be predicted with the developed analytical models.